2020
DOI: 10.1111/codi.15012
|View full text |Cite
|
Sign up to set email alerts
|

Mesorectal fat area and mesorectal area affect the surgical difficulty of robotic‐assisted mesorectal excision and intersphincteric resection respectively in different ways

Abstract: Aim Many studies have demonstrated predictors of the difficulty of laparoscopic anterior resection for rectal cancer. Few studies focus on the influence of pelvic dimensions on robotic-assisted mesorectal excision (ME) and intersphincteric resection (ISR). This study aimed to evaluate the influences of the mesorectal fat area (MFA) and mesorectal area on the difficulty of robotic sphincter-saving surgery. Methods We included 156 patients with middle and low rectal cancer who underwent robotic sphincter-saving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…As for racial differences in MFA, little is known because few studies thus far have evaluated MFA. Two studies conducted in Europe reported mean MFA values of 19.4 cm 2 and 20.7 cm 2 , respectively, which were consistent with our results [1,17]. On the other hand, Bolye et al [14] reported that the mean MFA values in an English population were 25.6 cm 2 in males and 18.4 cm 2 in females, whereas those in our study were 20.6 cm 2 and 16.67 cm 2 , respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As for racial differences in MFA, little is known because few studies thus far have evaluated MFA. Two studies conducted in Europe reported mean MFA values of 19.4 cm 2 and 20.7 cm 2 , respectively, which were consistent with our results [1,17]. On the other hand, Bolye et al [14] reported that the mean MFA values in an English population were 25.6 cm 2 in males and 18.4 cm 2 in females, whereas those in our study were 20.6 cm 2 and 16.67 cm 2 , respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Given the results of the aforementioned study as well as our own, aggressive adjuvant chemotherapy may be recommended to reduce recurrence rates in cases with small MFA. Smaller MFA was associated with higher recurrence rates, while larger MFA was related to increased surgical di culty in rectal cancer [15][16][17]. It is di cult to explain this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers found that low VAT was a poor prognostic marker because it could lead to impairment in nutritional supply and subsequent malnutrition [ 43 , 44 ]. In addition, higher PFA might affect the surgical difficulty of TME and intersphincteric resection, leading to poor oncological outcomes [ 45 ]. This was consistent with the results of our survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The de nitions of pelvic parameters measured from MRI before the primary surgery have been described previously, including the pelvic inlet length, the pubic tubercle height, the pelvic outlet length, the sacral length, the sacral depth, the interspinous distance, the mesorectal area and the rectal area [10,11].…”
Section: Pelvic Dimensionsmentioning
confidence: 99%